2018
DOI: 10.5650/jos.ess18143
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Synthesis-Promoting Effects of Andiroba Oil and its Limonoid Constituents in Normal Human Dermal Fibroblasts

Abstract: INTRODUCTION Carapa guianensis Aublet, a plant belonging to family Meliaceae, is popularly known in Brazil as andiroba 1 5. The seeds of this plant are the source of andiroba oil, which possesses a wide range of biological activities and ethnopharmacological uses 5 such as antibacterial 6 , anticancer 7 , antifungal 8 , insect repellent 9 , analgesic 10 , antimalarial 11 , anti-inflammatory 12 , antiallergic 13 , antiplasmodial 14 and antioxidative effects 15. During our characterization studies on the chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In our experiment, no increase in collagen synthesis was observed after treating fibroblasts with 6 μM BA. Another study on the stimulation of collagen synthesis in human fibroblasts by triterpenes has reported that gedunin (from Carapa guianensis seeds) increased collagen synthesis by 130% (14). Triterpene saponins from flowers of Bellis perennis also stimulate collagen synthesis in fibroblasts at the level of 130% compared to control (15).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our experiment, no increase in collagen synthesis was observed after treating fibroblasts with 6 μM BA. Another study on the stimulation of collagen synthesis in human fibroblasts by triterpenes has reported that gedunin (from Carapa guianensis seeds) increased collagen synthesis by 130% (14). Triterpene saponins from flowers of Bellis perennis also stimulate collagen synthesis in fibroblasts at the level of 130% compared to control (15).…”
Section: Discussionmentioning
confidence: 98%
“…Betula verrucosa, Centella asiatica, Bellis perennis, Carapa guianensis, Labisia pumila are plants used for centuries in folk medicine in various parts of the world to heal wounds and ulcers, and to relieve inflammation of the skin. The active ingredients present in this plant material have been well characterised, but studies examining the in vivo 33: 1087-1093 (2019) potential therapeutic properties of individual compounds are still ongoing (14)(15)(16). Other studies examining the effect of Calophyllim inophyllum, that contains triterpenes, on collagen production by primary fibroblasts have indicated stimulation of proliferation and collagen III production (17).…”
Section: Discussionmentioning
confidence: 99%
“…Deacetylgedunin is a limonoid (the 7-deacetyl derivative of gedunin) from Azadirachta indica known to possess anti-inflammatory and anti-malarial activities (Pereira et al, 2014; Sarigaputi et al, 2015; Akihisa et al, 2017; Chen et al, 2017). Deacetoxy-7-oxogedunin from Carapa guianensis , an analog of deacetylgedunin, was known for anti-malarial, hepatoprotective and collagen synthesis-promoting activities (Miranda Junior et al, 2012; Henriques and Penido, 2014; Pereira et al, 2014; Ninomiya et al, 2016; Morikawa et al, 2018). Dihydrotanshinone I is an analog of tanshinone IIA from S. miltiorrhiza with anti-cancer and anti-angiogenic activities (Zhang et al, 2012; Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ninomiya et al [113] believe that the mechanism of action of gedunin may involve inhibition of LPS-induced macrophage activation and reduction of sensitivity of hepatocytes to tumor necrosis factor-α (TNF-α), despite the fact that gedunin did not decrease the cytotoxicity caused by d-GalN. Recently, Morikawa et al [114], found that gedunin, isolated from C. guianensis seed oil, significantly promoted collagen synthesis in normal human dermal fibroblasts to 133.3, 134.7, and 136.8% at 3, 10, and 30 µM, respectively, without cytotoxicity at the same concentrations [114].…”
Section: Other Activitiesmentioning
confidence: 99%